From Ideological Flame to Rebellious Ashes: Analyzing the Emergence and Impact of Radical Ideology in the Arab World - Iyrot, Issam (Mazahib, 2025)
This study examines the historical and intellectual origins of radical thought in the Arab world and its evolution into organized armed movements. It investigates how ideas are selectively reinterpreted from one context to another: from Egyptian prisons where Takfir and Hijra were born to transnational jihadist organizations like Al-Qaeda and ISIS, to localized movements such as Hamas and Palestinian Islamic Jihad, synthesizing Qutbist categories with national liberation struggles under occupation. These results suggest that reducing radicalism to an issue of ideology is not feasible; instead, these legacies emanate from the interaction between doctrinal legacies and structural conditions, including authoritarian governance, foreign occupation, socio-economic marginalization, and the Arab state’s failure to manage diversity and uphold the rule of law. These conditions were so propitious that they facilitated both recruitment and legitimized radical discourse through framing violence as a religious duty and political necessity. By situating the emergence of radical thought within its historical context and examining its specific political and legal contexts, this research offers a more nuanced understanding of how universal ideological frameworks are established in diverse political and legal contexts. This study concludes that effective confrontation with radicalism must be an integrated approach, combining religious reform with the resolution of structural injustices that radical groups exploit in their mobilization efforts.